Endodontic Therapy in a Three Canal Mandibular Second Premolar - Asgary, Saeed (Iranian Endodontic Journal, 2010)
This article describes a clinical case of mandibular second premolar with three separated canals in apical third of the root that are diagnosed and endodontically treated. Sound knowledge of root canal anatomy and morphology, tactile examination of canal walls, critical interpretation of radiographs and high magnification examination are essential elements of success in complicated root canal therapy.